PERSEPSI SISWA SEKOLAH MENENGAH ATAS DAERAH ISTIMEWA YOGYAKARTA TERHADAP JURUSAN PERBANDINGAN AGAMA - Roni Ismail (UIN Sunan Kalijaga Yogyakarta, 2014)
The Department of Comparative Religion was established since 1961 as a center for the study of various religions and to promote brotherhood, humanity, and tolerance in the midst of religious plurality. This department was present to answer the basic needs of this pluralistic nation. However, the Department of Comparative Religion is not attracted many “market” including by the stu- dents from schools in Yogyakarta. This study aims to assess the perception of high school students in Yog yakarta which may be the cause of low interest in the study in this department. Data were collected by questionnaire (Summated Rating of Likert) which was distributed to 9 schools in Yog yakarta, each school 10 students were taken as samples. Analysis of the data processed with SPSS version 16. The results showed that students’ perceptions of the Department of Comparative Religion is Good with size <62.50 -> 81.25; 63.3% of respondents was aware of this and looking at the Department of Compara- tive Religion as the department of interest, 74.4% stated studied at the Department will strengthen the commitment of Islam, 81.1% regard this department is ver y important for Indonesian as a pluralistic nation. Therefore, 77.8% of respondents stated that the Comparative Religion as the name of department should be maintained. The factors that cause them to have a certain perception of the Department are: 21% of respondents are influenced by friends, 12.2% of respondents by teachers/preachers/cleric, 12.2% by parents, and 42.2% by social media for no lectures on Comparative Religion. Causative factor they are not intending to study in the Comparative Religion is not be- cause the name of the Department, but because of the employment prospects; 46.6% of respondents said the prospect of the department’s graduate employment is narrow, and 55.6% regard it as not in accordance with their dream. Although 76.7% of the respondents saw the name of Comparative Religion does not lead to the emergence of a negative perception, but 71.1% proposed to change the name the Department to reduce misunderstanding among wider community.